The political roots of health insurance benefit mandates. Issue 2 (8th May 2017) - Bailey, James; Webber, Douglas
Abstract : Purpose: As of 2011, the average US state had 37 health insurance benefit mandates, laws requiring health insurance plans to cover a specific treatment, condition, provider, or person. This number is a massive increase from less than one mandate per state in 1965, and the topic takes on a new significance now, when the federal government is considering many new mandates as part of the "essential health benefits" required by the Affordable Care Act. The paper aims to discuss these issues. Design/methodology/approach: The authors use fixed effects estimation on 1996-2010 data to determine why some states pass more mandates than others. Findings: The authors find that the political strength of health care providers is the strongest determinant of mandates. Originality/value: A large body of literature has attempted to evaluate the effect of mandates on health, health insurance, and the labor market. However, previous papers did not consider the political processes behind the passage of mandates. In fact, when they estimate the laws' effect, almost all papers on the subject assume that mandates are passed at random. The paper opens the way to estimating the causal effect of mandates on health insurance and the labor market using an instrumental variables strategy that incorporates political information about why mandates get passed.